Astragali radix total flavonoid synergizes cisplatin to inhibit proliferation and enhances the chemosensitivity of laryngeal squamous cell carcinoma. Issue 42 (7th August 2019) - Cui, Jiajia; Zheng, Xiwang; Yang, Dongli; Hu, Yinghuan; An, Changming; Bo, Yunfeng; Li, Huizheng; Zhang, Yuliang; Niu, Min; Xue, Xuting; Lu, Yan; Tang, Yemei; et al.
Abstract : Astragali radix total flavonoid synergizes with cisplatin to inhibit tumorigenesis of laryngeal squamous cell carcinoma. Abstract : Laryngeal squamous cell carcinoma (LSCC) is the most common head and neck cancer. Astragali radix extracts play crucial roles in the regulation of cancer progression. However, the role of Astragali radix extracts in LSCC and the related mechanisms remains unclear. Here, we evaluated the inhibitory effects of the combined use of Astragali radix total flavonoid (TFA) and cisplatin (CDDP) on an LSCC mouse model by pharmacodynamics. Ultra-high-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) was employed to define the prototype of TFA in vivo . The potential drug targets were identified through the integrative analysis of LSCC microarrays, RNA sequencing data and the main bioactive component of TFA. Furthermore, a protein–protein interaction network, compound–target network and target–pathway network were constructed based on the prototype and potential drug targets to identify the main targets and pathways. Animal experiments showed that TFA has significant synergistic antitumor activity with cisplatin and attenuates the nephrotoxicity caused by CDDP chemotherapy, improving the survival of LSCC-bearing mice. Using UPLC-MS/MS, we identified 8 constituents of TFA in experimental mice serum: formononetin, ononin, calycosin, calycosin-7- O -β-D-glucoside, 7, 2′-dihydroxy-3′, 4′-dimethoxyisoflavan, 7, 2′-dihydroxy-3′, 4′-dimethoxyisoflavaneglucoside, 3-hydroxy-9, 10-dimethoxypterocarpan and 9, 10-dimethoxyptercarpan-3- O -β-d -glucoside. Integrative analysis predicted 19 target genes for TFA constituents, and the target genes were mainly involved in the EGFR-related cancer signaling, metabolism and oxidative stress. Collectively, these findings highlight the role of TFA in the regulation of LSCC and provide potential targets for a high-efficiency and low-toxicity therapeutic strategy of LSCC.